A Study on the Research Trends of Big Data at Public Libraries : with a Focus on the Journal “Public Library Quarterly” - Lee, Seongsin; Kim, Hyunsook; Baeck, Sumin; Yoon, Subin (International Journal of Knowledge Content Development & Technology, 2022)
This study aims to analyze big data-related research trends in the public library field using the social network analysis method. One hundred seventeen articles published in the journal ‘Public Library Quarterly’ were analyzed with author keywords and the frequency, degree centrality, and betweenness centrality of the keywords were examined. The keywords “programs” and “community development” had the highest degree centrality. the keywords “programs,” “strategic planning,” “community development,” “future of libraries,” “outreach,” and “evaluation” post a high degree of centrality and betweenness centrality. The keywords “measurement,” “survey,” “community partnerships,” and “community engagement” showed a high degree of centrality but not high betweenness centrality. On the other hand, the keywords “planning,” “marketing,” “community needs,” and “community building” showed high betweenness centrality but not high degree centrality. Based on the results of this study, public libraries should focus on the following research directions when focusing on big data. First, as mentioned above, a more in-depth discussion is needed regarding COVID-19 and social media. Second, academic interest in big data education and training for public librarians and educational content is needed. Third, public libraries should think about ways to efficiently perform their role as a local data center, including cooperation with other organizations in the local community.